Effect of Reynolds Number on 90-Degree Short and Long Radius PVC Elbow Loss Coefficient - Rosli, Razlan; Idris, Ahmad Fu'ad; Azlan, Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study investigates the effect of the Reynolds number on the minor loss coefficients of 90-degree short and long-radius PVC elbows, which are crucial components in fluid transport systems. Experiments were conducted using a custom-fabricated setup to measure pressure drops and flow rates at varying Reynolds numbers. The findings reveal an inverse relationship between the Reynolds number and minor loss coefficients, indicating that energy losses decrease at a higher Reynolds number. Data analysis reveals that the most effective relationship between Reynolds number and loss coefficient value follows a cubic pattern. Furthermore, long-radius elbows consistently showed lower loss coefficients with a kL value of 1.11 compared to short-radius elbows with a kL value of 1.42 at a high Reynolds number, highlighting their greater efficiency in minimizing turbulence and pressure loss. These results contribute to the optimization of pipeline designs and provide valuable insights for creating more energy-efficient fluid transport systems in industrial applications.